(untitled) (JS (JURNAL SEKOLAH), 2023)
Abstract: Researchers in this case want to develop a learning evaluation by utilizing an evaluation media called Milanpulsa based on the Computer Adaptive Test (CAT). In this study, researchers used the Research and Development (R&D) method. The research subjects were educators and students at an elementary school, namely Ma’arif Pulutan Madrasah, Salatiga City. This research uses data collection instruments in the form of interviews & tests. The ADDIE model (Analysis, Design, Development, Implementation, and Evaluation) was used in this study. The product used will be developed according to the need assessment and then proceed to the feasibility testing level and revised so that it can be used until it is applied in the teaching and learning process. The results of the feasibility test or validation from the media validator obtain a percentage of 100% with a score of 4 while the material validator obtains a result of 95% with a score of 3.8. The results of the validator prove that the learning evaluation material using an evaluation media called Milanpulsa based on the Computer Adaptive Test (CAT) is feasible to use. The effectiveness of the Computer Adaptive Test (CAT)-based Milanpulsa evaluation media was obtained based on the results of the t test from the results of the pretest and posttest values. The results of the Paired Samples Statistics show the sig. 0.000 < 0.05 and t count = 10.061 > 2.043 then Ha is accepted and Ho is rejected. The striking difference between the pretest and posttest data, from the explanation above, it can be concluded that the development of learning evaluation using the Computer Adaptive Test (CAT)-based Milanpulsa exam media can improve the learning outcomes of class IV students at MI Ma’arif Pulutan, Salatiga City. Keywords: Learning Evaluation, Computer Adaptive Test, Authentic Assessment, Thematic Subjects, R&D Abstrak: Peneliti dalam hal ini ingin mengembangkan suatu evaluasi pembelajaran dengan memanfaatkan media Evaluasi yang bernama Milanpulsa berbasis Computer Adaptive Test (CAT). Dalam penelitian ini peneliti menggunakan metode Research and Development (R&D). Subjek penelitian yaitu pendidik dan peserta didik di sebuah madrasah ibtidaiyah yaitu Madrasah Ibtidaiyah Ma™arif Pulutan Kota Salatiga. Adapun penelitian ini menggunakan Instrumen pengumpulan data berupa wawancara & tes. Model ADDIE (Analysis, Desain, Development, Implementation, and Evaluation) digunakan dalam penelitian ini. Produk yang digunakan akan dikembangkan sesuai need asessment dan selanjutnya dilanjut ke tingkat pengujian kelayakan dan direvisi sehingga bisa digunakan sampai di aplikasikan dalam proses belajar mengajar. Hasil dari pengujian kelayakan ataupun validasi dari validator media memperoleh presentase 100% dengan skor 4 sedangkahn validator materi memperoleh hasil 95% dengan skor 3,8. Hasil validator membuktikan bahan evaluasi pembelajaran dengan menggunakan media Evaluasi bernama Milanpulsa berbasis Computer Adaptive Test (CAT) layak dipakai. Efektivitas media Evaluasi Milanpulsa berbasis Computer Adaptive Test (CAT) diperoleh berdasarkan hasil t test dari hasil nilai pretest dan postest. Hasil Paired Samples Statistics menunjukkan nilai sig. 0.000 < 0.05 dan t hitung = 10,061 > 2,043 maka Ha diterima dan Ho ditolak. Perbedaan yang mencolok dari data pretest dan posttest, dari penjelasan diatas dapat disimpulkan bahwa pengembangan evaluasi pembelajaran menggunakan media ujian Milanpulsa berbasis Computer Adaptive Test CAT) dapat meiningkatkan hasil belajar siswa kelas IV MI Ma™arif Pulutan Kota Salatiga. Kata Kunci: Evaluasi Pembelajaran, Computer Adaptif Test, Penilaian Autentik, Mata Pelajaran Tematik, R&D